Effect of Salinity and Oxygen Condition on Phosphate Release from Marine Sediment Measured Using Diffusive Gradient in Thin Film (DGT) Technique - Askal Maimulyanti; Budiawan Budiawan; Asep Saefumillah; Heny Suseno (Indonesian Journal of Chemistry, 2019)
The diffusive gradient in thin film (DGT) is an analytical technique to determine phosphate in the environment. This technique uses a thin film diffusive hydrogel in contact with a binding phase (ferrihydrite) to binding of phosphate. The released phosphate from marine sediment of Jakarta Bay was studied by DGT technique for effect of salinity and oxygen condition. Effect of salinity was observed by NaCl concentration from 0-35 g/L. The maximum phosphate release from sediment was occurred at the concentration of NaCl 30 g/L with incubation for 15 days with phosphate released at 113.99 μg/L, MDGT of 4.7723 μg and CDGT of 17.56 μg/L. The experiment showed the increase of MgCl2 and CaCl2 concentration reduced phosphate release from sediment. The condition of oxygen indicating the release of phosphate under anaerobic conditions is greater than the aerobic condition. The aerobic conditions with incubation for 21 days showed the release of phosphate from sediment to overlying water of 124.72 μg/L, MDGT of 2.4492 μg and CDGT of 6.4380 μg/L. Anaerobic conditions with incubation for 21 days showed phosphate release from sediment to overlying water of 208.62 μg/L, MDGT of 6.1081 μg and CDGT of 16.06 μg/L. The experiment shows that salinity and oxygen concentration influences phosphate release from marine sediment of Jakarta Bay.